Profile of maxillofacial injuries in Departement of Emergency Trauma and Acute Care Surgery in Sanglah General Hospital from January 2012 to November 2018 - Anak Agung Gde Agung Anom Arie Wiradana; Ketut Wiargitha (Intisari Sains Medis, 2019)
Introduction: Maxillofacial injuries are common cause of trauma in emergency department. The goals in the treatment of maxillofacial injury are to restore premorbid occlusion. This study aimed to evaluate the characteristics and outcome of the maxillofacial injuries patient in Sanglah General Hospital Denpasar Bali.Methods Retrospective study was held in Sanglah General Hospital from January 2012 to November 2018. The samples consisted of 241 patients. Age, gender, type of the fractures and surgical management were evaluated.Results Maxillofacial injuries mostly occurred in male, aged 18-40 years old, the mandible was most frequently involved facial bone. Â Internal fixation was the golden standard of the treatment chosen (83.73%) followed by Arch bar (16.27%).Conclusion Road traffic accidents are the main reason for maxillofacial injury in Sanglah General Hospital Denpasar Bali. Precise diagnosis and proper treatment result in optimal occlusion and integrity nervous system, both internal fixation and arch bar were given good outcome.